Analysis Of Tourism Attractions, Tourism Image, And Promotion On Visit Decisions At The Bukit Lawang Water Tourism Destination - Olim Hanafiah Napitupulu; Yana Diana; Yossie Rossanty (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of tourist attractions, destination image, and promotion on tourists’ visiting decisions at the Bukit Lawang water tourism destination. The study employs a quantitative approach using a survey method. The research instrument is a Likert-scale questionnaire. The sampling technique uses purposive sampling involving tourists who have visited Bukit Lawang. Data analysis methods include descriptive statistics, validity testing, reliability testing, classical assumption tests, and multiple linear regression analysis. Data processing is conducted using the SPSS application. The results indicate that tourist attractions and destination image have a positive and significant partial effect on visiting decisions. Promotion has a positive but not significant effect on visiting decisions. Simultaneously, tourist attractions, destination image, and promotion have a significant effect on visiting decisions. Destination image is the most dominant variable influencing tourists’ visiting decisions.